Alternative splicing of the human gene SYBL1 modulates protein domain architecture of longin VAMP7/TI-VAMP, showing both non-SNARE and synaptobrevin-like isoforms - Vacca, Marcella (BioMed Central, 2011)
BACKGROUND: The control of intracellular vesicle trafficking is an ideal target to weigh the role of alternative splicing in shaping genomes to make cells. Alternative splicing has been reported for several Soluble N-ethylmaleimide-sensitive factor Attachment protein REceptors of the vesicle (v-SNAREs) or of the target membrane (t-SNARES), which are crucial to intracellular membrane fusion and protein and lipid traffic in Eukaryotes. However, splicing has not yet been investigated in Longins, i.e. the most widespread v-SNAREs. Longins are essential in Eukaryotes and prototyped by VAMP7, Sec22b and Ykt6, sharing a conserved N-terminal Longin domain which regulates membrane fusion and subcellular targeting. Human VAMP7/TI-VAMP, encoded by gene SYBL1, is involved in multiple cell pathways, including control of neurite outgrowth. RESULTS: Alternative splicing of SYBL1 by exon skipping events results in the production of a number of VAMP7 isoforms. In-frame or frameshift coding sequence modifications modulate domain architecture of VAMP7 isoforms, which can lack whole domains or domain fragments and show variant or extra domains. Intriguingly, two main types of VAMP7 isoforms either share the inhibitory Longin domain and lack the fusion-promoting SNARE motif, or vice versa. Expression analysis in different tissues and cell lines, quantitative real time RT-PCR and confocal microscopy analysis of fluorescent protein-tagged isoforms demonstrate that VAMP7 variants have different tissue specificities and subcellular localizations. Moreover, design and use of isoform-specific antibodies provided preliminary evidence for the existence of splice variants at the protein level. CONCLUSIONS: Previous evidence on VAMP7 suggests inhibitory functions for the Longin domain and fusion/growth promoting activity for the Δ-longin molecule. Thus, non-SNARE isoforms with Longin domain and non-longin SNARE isoforms might have somehow opposite regulatory functions. When considering splice variants as "natural mutants", evidence on modulation of subcellular localization by variation in domain combination can shed further light on targeting determinants. Although further work will be needed to characterize identified variants, our data might open the route to unravel novel molecular partners and mechanisms, accounting for the multiplicity of functions carried out by the different members of the Longin proteins family.